2020
DOI: 10.3390/buildings10020031
|View full text |Cite
|
Sign up to set email alerts
|

Urban Residential Building Energy Consumption by End-Use in Malawi

Abstract: Buildings account for about 40% of the global energy consumption and this energy demand is projected to continue growing over the next few decades. Residential buildings are responsible for over 60% of this consumption pattern with commercial buildings being responsible for the remainder. While residential building energy consumption constitutes about 20% of the total consumption in the developed world, it constitutes up to more than 50% in the sub-Sahara African region. The growing consumption of energy has r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Secondly, climate change in general and variation in degree days in specific are known to be the result of GHG emissions. Since operation of the building sector depends on the combustion of fossil fuels, the main source of GHG emissions, directly (i.e., coal, natural gas, petroleum) and indirectly (electricity generation) [66,67], there is probably a reciprocal cause and effect between variation in degree days and building energy use. This is another reason for insignificant energy use intensity change of six studied years.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, climate change in general and variation in degree days in specific are known to be the result of GHG emissions. Since operation of the building sector depends on the combustion of fossil fuels, the main source of GHG emissions, directly (i.e., coal, natural gas, petroleum) and indirectly (electricity generation) [66,67], there is probably a reciprocal cause and effect between variation in degree days and building energy use. This is another reason for insignificant energy use intensity change of six studied years.…”
Section: Discussionmentioning
confidence: 99%
“…However, improvements in indoor thermal comfort are often accompanied by increases in building energy consumption and environmental pollution [3,4]. It is reported that buildings account for 40% of the total global energy consumption, and this proportion is still increasing [5,6]. In addition, approximately 40% of the total human greenhouse gas emission is attributed to the building industry [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Buildings are not only amongst the largest drivers of global energy demand [1][2][3][4][5][6], but can also create sharp peaks in demand [7][8][9], which critically affects the reliability of supply infrastructure [10][11][12][13][14][15][16]. Network peaks fundamentally occur due to simultaneous power draws over short periods of time.…”
Section: Introductionmentioning
confidence: 99%